2017
DOI: 10.1111/nyas.13559
|View full text |Cite
|
Sign up to set email alerts
|

Cobinamide is effective for treatment of hydrogen sulfide–induced neurological sequelae in a mouse model

Abstract: Hydrogen sulfide (H2S) is a highly neurotoxic gas. Acute exposure can lead to neurological sequelae among survivors. A drug for treating neurological sequelae in survivors of acute H2S intoxication is needed. Using a novel mouse model we evaluated the efficacy of cobinamide (Cob) for this purpose. There were two objectives: (1) to determine the dose–response efficacy of Cob and (2) to determine the effective therapeutic time window of Cob. To explore objective 1, mice were injected intramuscularly with Cob at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…13 Cobinamide reacts quickly with H 2 S to form a stable complex (SSH 2 -). [21][22][23][24] In a large swine model of high-dose, inhaled H 2 S gas, we found that intramuscular aminotetrazole cobinamide rescued all animals when administered at the very end of sulfide exposure. Admittedly, this is not the same as being treated in a hospital sometime after sulfide exposure, but if the antidote were available in the field, it could be administered at the same time as removal of victims from the H 2 S source.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…13 Cobinamide reacts quickly with H 2 S to form a stable complex (SSH 2 -). [21][22][23][24] In a large swine model of high-dose, inhaled H 2 S gas, we found that intramuscular aminotetrazole cobinamide rescued all animals when administered at the very end of sulfide exposure. Admittedly, this is not the same as being treated in a hospital sometime after sulfide exposure, but if the antidote were available in the field, it could be administered at the same time as removal of victims from the H 2 S source.…”
Section: Discussionmentioning
confidence: 76%
“…Cobinamide was found to improve survival and offer neuroprotection in mice when administered after H 2 S exposure. 21 Brenner et al and Ng et al showed that intramuscular administration of cobinamide improves survival in sulfide-poisoned rabbits and pigs, respectively, but in both cases, the animals were injected with intravenous NaHS. 23,26 In this study, exposure to H 2 S occurred via the inhaled route, which is the most common route of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations